ANALISA RANCANGAN BAND REJECTION FILTER UNTUK WIMAX FREKUENSI 3.5 GHz - Linna Oktaviani Sari; Ery Safrianti; Fauzi Hidayat (Sainstek (e-Journal), 2016)
The development of technology-based 4G Broadband Wireless Access (BWA) is growing rapidly. In the BWA network isrequired high-speed connection and large capacity to access the internet compared to previous 3.5G technology. Oneof technology in the 4G BWA grown today is WiMAX IEEE 802.16d standard. WiMAX IEEE 802.16d standard is usingthe 3.5 GHz frequency. In this frequency, WiMAX have problems to be applied in Indonesia. This is due to the satellitein Indonesia use the same frequency with the WiMAX frequencies. For the implemention in Indonesia, it is necessary todesign a band rejection filter to avoid interference between Imax and satellite. This research has been analyzed and designed Band rejection filter using the software Advanced Design System (ADS) 2011.01. The Responses are used inthis design is Chebyshev response, because the Chebyshev response can produce a high degree of steepness. The resultsshowed that the design of band rejection filter can refuse satellite frequency at a frequency of 3.5 GHz in the range of30-50 dB with bandwitdh 120 MHz.